Hierarchical biomechanical characterisation of riboflavin-UVA crosslinking and decorin treatment in the porcine cornea - Bell, J. S.; Morgan, S. R.; Shebanova, O.; Evans, S. L.; Boote, C.; Terrill, N.; Meek, K. M.; Hayes, S. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThe mechanisms underpinning the stiffening and stabilising effect of riboflavin/UVA crosslinking on the corneal stroma are not well understood. We report the findings of a biomechanics and synchrotron X-ray scattering study aimed at quantifying hierarchical strain mechanisms in treated and untreated porcine corneas. We applied the same approach to specimens treated with human recombinant decorin core protein, in isolation and in conjunction with riboflavin/UVA.MethodsTensile testing was carried out in conjunction with simultaneous synchrotron X-ray scattering. Diffraction peaks associated with the interfibrillar spacing and D-period of collagen were fit to bespoke models to quantify fibril elongation and reorientation under load.ResultsRiboflavin/UVA crosslinking stiffened corneas by approximately 60% while decorin treatment did not significantly affect the mechanical properties. Correlations between fibril elongation caused by applied tensile strain and bulk stiffness were used to approximate fibril stiffness, values for which were relatively similar for control and treatment groups, compared with the magnitude of difference in the bulk stiffness alone.DiscussionThe results imply the bulk stiffening caused by crosslinking was not primarily due to increases in fibril stiffness. Instead, trends in bulk fibril reorientation and straightening/uncrimping imply the stiffening is attributable to enhanced interconnectivity of the fibrillar stroma, leading to greater fibril recruitment fraction. The techniques reported here are applicable to a wide range of tissues for the evaluation of new, existing and adjuvant therapies.